Needle decompression of tension pneumothorax: Population-based epidemiologic approach to adequate needle length in healthy volunteers in Northeast Germany. Issue 1 (January 2016) - Hecker, Matthias; Hegenscheid, Katrin; Völzke, Henry; Hinz, Peter; Lange, Jörn; Ekkernkamp, Axel; Frank, Matthias
Abstract : BACKGROUND: Tension pneumothorax is one of the leading causes of preventable death in both military and civilian trauma patients. Needle decompression is recommended in trauma guidelines as an emergency procedure to relieve increased intrapleural pressure. The main reason for decompression failure is reported to be insufficient needle length in proportion to the chest wall thickness (CWT). So far, population-based epidemiologic data on CWT are missing. Therefore, it was the aim of this work to investigate the CWT in the second intercostal space, midclavicular line, based on magnetic resonance imaging data of a large population-based sample. The second aim of this study was to explore the potential risk of iatrogenic lesions caused by the proximity of the intended puncture track to the internal mammary artery. METHODS: A total of 2, 574 healthy volunteers (mean [SD] age, 53.3 [13.9] years; range, 21–89 years) from the population-based cohort Study of Health in Pomerania (SHIP) were enrolled. CWT and the distance from the intended puncture track to the internal mammary artery were investigated with the chest sequences of a standardized 1.5-T whole-body magnetic resonance imaging. RESULTS: For all 5, 148 measured sites in 2, 574 volunteers, the mean (SD) CWT was 5.1 (1.4) cm. The mean body mass index was determined to be 27.7 kg/m 2 . The CWT correlated significantly with body weight and body mass index. The internal mammary artery was located medial to the intended puncture site in all participants; the mean (SD) distance was 5.7 (0.7) cm on the right and 5.5 (0.7) cm on the left side. CONCLUSION: Based on the population-based epidemiologic data presented in this study, the use of a needle of 7 cm in length is recommended to decompress a tension pneumothorax in the second intercostal space in the midclavicular line, which might successfully decompress more than 90% of the participants in this study. When using this anterior approach at the anatomically correct puncture site, safety margin to the internal mammary artery is sufficient so that the risk of iatrogenic lesion of the internal mammary artery should be minimal. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV. Abstract : Supplemental digital content is available in the text.